2019
DOI: 10.1364/oe.27.031840
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high-quality terahertz OAM mode based on soft-aperture difference frequency generation

Abstract: We demonstrate the generation of high-quality tunable terahertz (THz) vortices in an eigenmode by employing soft-aperture difference frequency generation of a vortex output and a Gaussian mode. The generated THz vortex output exhibits a high-quality orbital angular momentum (OAM) mode with a topological charge of ℓTHz = ±1 in a frequency range of 2-6 THz. The maximum average power of the THz vortex output obtained was ~3.3 µW at 4 THz.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 72 publications
(70 reference statements)
1
22
0
Order By: Relevance
“…The selection rules we have established are in agreement with Refs. [28,29] for the DFG case and also in agreement with Refs. [30,31] for the OR case, where it has been experimentally demonstrated that, unless further modifications to the optical system are performed, the expectation value for the OAM of the OR field is zero.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The selection rules we have established are in agreement with Refs. [28,29] for the DFG case and also in agreement with Refs. [30,31] for the OR case, where it has been experimentally demonstrated that, unless further modifications to the optical system are performed, the expectation value for the OAM of the OR field is zero.…”
supporting
confidence: 91%
“…The authors of Refs. [28,29] demonstrate that in their DFG experimental conditions, the transduction of OAM occurs under the conservation of OAM. Concerning this Letter, we have found that it is related to the conservation of the total angular momentum; therefore, our result is a generalization in this sense, because it does not apply only to the case of linear polarization of the pump.…”
mentioning
confidence: 98%
“…If we look to the results of other authors obtained in a similar problem, we can see that this scheme is actively studied and successfully tested experimentally. Thus, in [5], the conversion of an OAM signal from the optical to the terahertz spectral region was experimentally studied using a quadratic-nonlinear element. The relations for the output signal parameters, in particular, the OAM topological charge (ℓTHz) and the conversion efficiency η DFG , are also obtained there, see ( 2) and (3).…”
Section: Analysis Of Optical Quadratic-nonlinear Materials and Structures Potentially Suitable For The Design Of A Nonlinear Convertermentioning
confidence: 99%
“…Yet, it only can be adopted in a certain frequency. Moreover, THz vortex beams can be indirectly generated by optical vortex-pumped difference frequency generation (DFG) in a nonlinear crystal [22], [23] or vortex-laser-induced air plasma [24], [25].…”
Section: Introductionmentioning
confidence: 99%